Sensory acceptance of “Mackerel Burger” with reduced salt content as an alternative for school feeding - Quadros, Diomar Augusto de; Bolini, Helena Maria André (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2022)
This study aimed to evaluate consumers’ acceptance of Serra Spanish Mackerel burgers (Scomberomorus brasiliensis) with reduced sodium content for school feeding programs. The variables studied were fish pulp (whole and washed) and concentration of table salt (1.5% and 0.75%) and monosodium glutamate (0% and 0.3%). The samples were subjected to the determination of sodium content and consumers’ acceptance test with both adults and children. The tests with adult consumers were performed in two Brazilian cities: Campinas, São Paulo State, and Matinhos, Paraná State, while the tests with children were carried out only in Matinhos city. The results were evaluated through an analysis of variance, Tukey’s test (p ≤ 0.05) and a frequency distribution bar graph. The tests with adults from both cities were compared by Student’s t-test (p < 0.05). Significant differences were observed in the sodium content of all formulations, which ranged from 199.26 mg/100 g (F7) to 517.76 mg/100 g (F2). Significant differences (p < 0.05) were observed in the acceptance tests with adult consumers for the attributes appearance, flavor, and overall impression between the two cities by t-test. For the consumer test with children, no significant difference was observed, with scores ranging from 6.67 to 6.75. The data suggest that the fish burgers can be part of school meals.